Formação, atuação profissional e mercado de trabalho em administração: o caso dos egressos do curso de graduação da UFSM - Regio, Maria de Lourdes Severo (2011)
The qualification of Directors of Education requires a thorough evaluation of the training being developed. An effective evaluation of a college degree necessarily involves the analysis of its graduates. The Undergraduate Program in Business Administration from Universidade Federal de Santa Maria - UFSM object of this study, it was the reality of its graduates surveyed. The previous study, Management and Training Labor Market, was written by Vitor Francisco Junior Schuch in 1978. In this context, the present study was conducted along with the alumni of the course of Directors - UFSM formed in the period 2005 to 2009. The results expected from this research was the knowledge of the reality of their work identifying 359 graduates of career development, the difficulties and expectations of continuing education. The objective was to identify the graduates in the market and analyze the skills front of his academic background and how the course contributes to the development of skills that the curriculum intended. The strategy used in this study can be characterized as a case study with quantitative descriptive approach, as intended to study and describe characteristics of the researched reality. The data collection survey was conducted through two structured questionnaires. The questionnaire I was destined to graduates who are working in the profession, and is divided into four parts. The questionnaire II was directed to the graduates who were not working in the profession containing two blocks. The main result that contacted the majority of graduates of the course of Directors of UFSM is not performing the occupation for which they were prepared to compare with the study in 1978. This finding may be due to the significant expansion of Higher Education Institutions - IES Administration in Brazil. Another reason for the failure to exercise the profession, based on survey data is that the vast majority of those who are not exercising the profession have obtained work activity other than a graduate or remain in employment who performed before completing the course. The results also indicate the development of skills suggested by the proposed national curriculum guidelines for the Administration Course for graduation.